2020
DOI: 10.1007/s00167-020-05922-9
|View full text |Cite
|
Sign up to set email alerts
|

Large variability exists in the management of posterolateral corner injuries in the global surgical community

Abstract: Purpose The management of posterolateral corner (PLC) injuries has significantly evolved over the past 2 decades. The purpose of this study was to determine the current worldview of key concepts on the diagnosis, treatment strategy, and rehabilitation for patients presenting with PLC injuries. Methods A 12-question multiple-choice online survey was designed to address key questions in the diagnosis, treatment, and rehabilitation of PLC injuries. The survey was distributed to the most important international sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Similar to previous survey studies, statistical analyses were not performed. 14 , 15 , 16 , 17 Clinical agreement among responses was defined by a minimum of 80% agreement in responses, whereas general agreement was defined as a minimum of 60% agreement. 14 , 18 , 19 Responses were analyzed according to practice type, provider sex, and fellowship training (pediatric orthopaedics, sports medicine, or dual pediatric orthopaedics and sports medicine).…”
Section: Methodsmentioning
confidence: 99%
“…Similar to previous survey studies, statistical analyses were not performed. 14 , 15 , 16 , 17 Clinical agreement among responses was defined by a minimum of 80% agreement in responses, whereas general agreement was defined as a minimum of 60% agreement. 14 , 18 , 19 Responses were analyzed according to practice type, provider sex, and fellowship training (pediatric orthopaedics, sports medicine, or dual pediatric orthopaedics and sports medicine).…”
Section: Methodsmentioning
confidence: 99%
“… 34 This is likely a result of these injuries most often presenting as part of a variety of different complex multiligamentous injuries rather than in isolation, as well as their lower incidence in comparison to single-ligament injuries. 35 In a recent international expert consensus review on the PLC, Chahla et al identified multiple areas reaching an expert consensus such as diagnostic aids, timing of treatment, and the need for anatomical reconstruction of injured structures. 34 …”
Section: Treatmentmentioning
confidence: 99%
“…Various methods of PLC reconstruction have been reported regarding the structures, the type of grafts and the fixations. 1 However, an easily performed procedure is still needed, 2 and there is still much room for improvement regarding the clinical results. 3 , 4 , 5 Thus, we would like to introduce a PLC reconstruction technique in which a single tendon is used to reconstruct or augment the LCL, the PFL and the PT, and 1 femoral tunnel is created for the reconstruction of all 3 structures.…”
Section: Introductionmentioning
confidence: 99%